Chemical analysis of refractory stratospheric aerosol particles collected within the arctic vortex and inside polar stratospheric clouds - Ebert, Martin; Weigel, Ralf; Kandler, Konrad; Günther, Gebhard; Molleker, Sergej; Grooß, Jens-Uwe; Vogel, Bärbel; Weinbruch, Stephan; Borrmann, Stephan (Atmospheric Chemistry and Physics, 2018)
Stratospheric aerosol particles with diameters larger than about 10 nm were collected within the arctic vortex during two polar flight campaigns: RECONCILE in winter 2010 and ESSenCe in winter 2011. Impactors were installed on board the aircraft M-55 Geophysica, which was operated from Kiruna, Sweden. Flights were performed at a height of up to 21 km and some of the particle samples were taken within distinct polar stratospheric clouds (PSCs). The chemical composition, size and morphology of refractory particles were analyzed by scanning electron microscopy and energy-dispersive X-ray microanalysis. During ESSenCe no refractory particles with diameters above 500 nm were sampled. In total 116 small silicate, Fe-rich, Pb-rich and aluminum oxide spheres were found. In contrast to ESSenCe in early winter, during the late-winter RECONCILE mission the air masses were subsiding inside the Arctic winter vortex from the upper stratosphere and mesosphere, thus initializing a transport of refractory aerosol particles into the lower stratosphere. During RECONCILE, 759 refractory particles with diameters above 500 nm were found consisting of silicates, silicate ∕ carbon mixtures, Fe-rich particles, Ca-rich particles and complex metal mixtures. In the size range below 500 nm the presence of soot was also proven. While the data base is still sparse, the general tendency of a lower abundance of refractory particles during PSC events compared to non-PSC situations was observed. The detection of large refractory particles in the stratosphere, as well as the experimental finding that these particles were not observed in the particle samples (upper size limit ∼ 5 µm) taken during PSC events, strengthens the hypothesis that such particles are present in the lower polar stratosphere in late winter and have provided a surface for heterogeneous nucleation during PSC formation.